Mentor Texts and the Coding of Academic Writing Structures: A Functional Approach - Wilder Yesid Escobar Alméciga; Reid Evans (Asociación Colombiana de Profesores de Ingles, 2014)
The purpose of the present pedagogical experience was to address the English language writing needs of university-level students pursuing a degree in bilingual education with an emphasis in the teaching of English. Using mentor texts and coding academic writing structures, an instructional design was developed to directly address the shortcomings presented through a triangulated needs analysis. Through promoting awareness of international standards of writing as well as fostering an understanding of the inherent structures of academic texts, a methodology intended to increase academic writing proficiency was explored. The study suggests that mentor texts and the coding of academic writing structures can have a positive impact on the production of students' academic writing.